Skandinavisk sci-fi-poesi: Med særligt henblik på aktuel cli-fi-poesi - Mønster, Louise (Passage - Tidsskrift for litteratur og kritik, 2019)
The article gives an introduction to the use of sci-fi and cli-fi in Scandinavian poetry. By focusing on seven works from Denmark, Sweden and Norway, the article discusses different ways in which sci-fi, and especially cli-fi, has become a significant element in poetry preoccupied with contemporary social, technological and environmental issues.